The Stannides Nd3Pd5Sn5, Gd3Pd4.96(1)Sn5, and GdPdSn1. Issue 2 (7th November 2014) - Heying, Birgit; Rodewald, Ute Ch.; Pöttgen, Rainer
Abstract The stannides Nd3Pd5Sn5 and Gd3Pd4.96(1)Sn5 were obtained by arc‐melting of the elements. Nd3Pd5Sn5 and Gd3Pd4.96(1)Sn5 crystallize with the monoclinic Sm3Pd4.95Sn5 type structure, space group C2/m. Both structures were refined from single crystal diffractometer data: a = 1729.5(4), b = 454.51(8), c = 1428.2(3) pm, β = 99.71(2)°, wR2 = 0.0689, 2220 F2 values, 82 variables for Nd3Pd5Sn5 and a = 1712.2(2), b = 450.36(9) c = 1412.0(3) pm, β = 99.804(2)°, wR2 = 0.0526, 1834 F2 values, 83 variables for Gd3Pd4.96(1)Sn5. The Pd2 site of the gadolinium compound showed site occupancy of only 95.8(7) %. The palladium and tin atoms in these monoclinic stannides build up complex three‐dimensional [Pd5Sn5]δ– polyanionic networks, which leave cavities for the three crystallographically independent rare earth sites: RE1@Pd6Sn8, RE2@Pd7Sn8, and RE3@Pd6Sn9. The networks are stabilized by Pd–Sn, Pd–Pd as well as Sn–Sn bonding. The rare earth atoms bind to the networks via shorter RE–Pd contacts. The Gd3Pd4.96(1)Sn5 crystal showed an adherent second domain, which consisted of GdPdSn: TiNiSi type, Pnma, a = 725.6(3), b = 461.3(3), c = 790.6(3) pm, wR2 = 0.0973, 431 F2 values, 20 variables.